The Non-injured Leg Can Be Used as a Reference for the Injured Leg in Single-legged Hop Tests - Astrid Vereijken; Emiel van Trijffel; Inne Aerts; Bruno Tassignon; Jo Verschueren; Romain Meeusen (North American Sports Medicine Institute, 2021)
# Background Single-legged hop tests are frequently used in substantiating return to sport decisions following lower extremity injury. Evidence for using the non-injured leg as a reference for the injured leg in the return to sport decision-making at the criterion-based point of return to sport following lower extremity injury is lacking. # Purpose To compare absolute values in single-legged hop tests between the non-injured leg of athletes returning to high-impact sports after lower extremity injury and the matched leg of healthy athletes. # Study Design Cross-sectional study. # Methods One hundred and sixty-nine athletes returning to high-impact sports after lower extremity injury and 169 matched healthy athletes executed five single-legged hop tests. Differences between athletes returning to high-impact sports after lower extremity injury and matched healthy athletes on five single-legged hop tests were analyzed using paired t-tests. # Results There were no statistically significant differences between the non-injured leg of athletes returning to sport and the matched leg of healthy athletes. Effect sizes ranged from 0.05 to 0.14 indicating negligible effects. # Conclusion Clinicians can use the non-injured leg as a reference for the injured leg in single-legged hop tests for deciding on return to high-impact sports after lower extremity injuries. # Level of Evidence 3b